Comparative Genomic Analysis of Two Xanthomonas oryzae pv. oryzae Strains Isolated From Low Land and High Mountain Paddies in Guangxi, China - Li, Tianjiao; Li, Yiming; Ma, Xiuguo; Dan, Xue; Huang, Xianjiao; Li, Qinying; Lei, Shimin; Zhang, Zhengchun; Huang, Sheng; Jiang, Wei; Yu, Yanhua; He, Yong-Qiang (Frontiers in Microbiology, 2022)
Xanthomonas oryzae pv. oryzae (Xoo) is causal agent of rice bacterial leaf blight (BLB), the major rice disease seriously constraining the rice production in Asia. The interaction between Xoo and rice is in a dynamic process, essentially the co-evolution. Tracking the BLB occurrence and timely identifying the epidemic Xoo strains is essential for understanding of the potential genetic variation in the evolution of the pathogen. In 2020, the occurrences of rice BLB were spotted in many places of Guangxi, the major rice growing region in China. Two 2020-epidemic Xoo strains, namely GXO20-01 and GXO20-16, isolated from low land and high mountain paddies in Guangxi, respectively, were demonstrated to be race R8 of Chinese Xoo strains, but with significantly different virulence on certain susceptible rice varieties. The HiFi PacBio sequencing revealed that GXO20-01 and GXO20-06 share the highly syntenous genome structures and the major genome contents, but only differ in less than ten genes, including one gene encoding for transcription activator-like effector (TALE). Phylogenomic analysis grouped GXO20-01 and GXO20-06 into the PX-A linage, close to PXO563 and PXO71 strains, but away from the other Chinese Xoo strains, e.g. the JL25 and YC11. Comparative genomic analysis revealed that the major pathogenicity/virulence genes are conserved in two newly isolated Xoo strains and the other Xoo strains in PX-A linage, including the majority genes for the TALomes. The genomic differences between the Xoo strains are pinpointed to a few tal genes, which are variable in both their numbers and sequences, even between GXO20-01 and GXO20-06, the two 2020-epidemic Xoo strains. The study further revealed the instability and variability of tal genes in Xoo and highlighted the utility of HiFi long-read sequencing in TALE analysis and pathogen tracking.